The Design of Spin Catalysts: Breakthroughs toward Efficient Energy Conversion - Yantao Yang; Yufeng Li; Baipeng Yin; Chuang Zhang (ChemElectroChem)
In energy conversion technologies, the electron spin effect in catalysts plays a crucial role in overcoming spin‐forbidden reactions, offering a novel approach to overcome the performance bottlenecks of catalysts. Recently, with breakthroughs in magnetic field–enhanced catalysis and theoretical predictions, significant progress has been made in the design and development of spin catalysts. In this concept, several attractive and inspiring spin catalyst design strategies reported recently, particularly the precise modulation of spin states/spin interactions at catalytic sites through coordination modulation, spin‐pinning effect, chirality induction, and radical adsorption, are outlined. The concept then explores the advantages of these design strategies in enhancing catalytic activity/selectivity, investigating spin selectivity in reaction pathways, and expanding catalytic reaction systems. Finally, the concept proposes future development directions for spin catalysts in energy conversion technologies.